Uptake of Family-Specific Mutation Genetic Testing Among Relatives of Patients with Ovarian Cancer with BRCA1 or BRCA2 Mutation - Jeong, Go Woon; Shin, Wonkyo; Lee, Dong Ock; Seo, Sang-Soo; Kang, Sokbom; Park, Sang-Yoon; Lim, Myong Cheol (Cancer research and treatment, 2021)
PurposeThe BRCA1 or BRCA2 gene is transmitted in an autosomal dominant fashion, and genetic testing of first-degree relatives of patients with family-specific mutation (FSM) is recommended. This study examined factors affecting the uptake of FSM testing among relatives of patients with peritoneal, ovarian, or fallopian tube (POFT) cancer with confirmed BRCA1 or BRCA2 germline mutation.Materials and MethodsData from medical charts of 392 eligible patients and their relatives who had undergone outpatient genetic counseling/testing were retrospectively reviewed. Clinical factors were compared between family members who had and had not undergone genetic counseling/testing.ResultsThe uptake of FSM testing was 30.5% (129/423) among first-degree living relatives and 53.5% (69/129) within the overall family unit. The average time from genetic testing of the proband to the first FSM test within a family was 168 days (range, 23 to 681 days). Having a living father (33.8% vs. 13.3%, p=0.007) and daughter (79.4% vs. 60.3%, p=0.019) increased the uptake of FSM testing. FSM testing was more likely among female than among male relatives of cancer patients (40.9% vs. 17.6%, p < 0.001).ConclusionApproximately one-third of first-degree relatives of patients with a POFT cancer with BRCA1 or BRCA2 mutation underwent FSM testing. Having a living father or daughter was a factor affecting the uptake of FSM testing, which was higher among female than among male relatives of the proband. This discrepancy might be due to a misconception that the BRCA gene is associated with women rather than with men.